THE ROLE OFACADEMIC LAW LIBRARIES IN MEETING INFORMATION NEEDS OF LEGAL CLIENTELE (NAU Journal of Library and Information Science, 2021)
This paper sought to highlight and discuss the dynamic role of academic law libraries in meeting the information needs of judges, lawyers, law students and law firms. The paper restated the crucial role law libraries play in legal education, legal research and administration of Justice. The paper further examined the challenges academic law libraries face in meeting the information needs of its users. Major challenges these libraries face in meeting the information needs of its users include paucity of funds, lack of qualified personnel, poor ICT facilities, poor preservation and maintenance culture, among others. Based on these constraints, recommendations were made on how to improve the services of these libraries. Keywords: Law library, Legal Education, Legal Profession, Lawyers, Law Students. IntroductionSimply put, a law library is a library whose collection and services are tailored to meet the information and research needs of persons in the legal profession; be it lawyers, judges, law students or legal researchers. It is thus a special library both by its content and services. There are different types of law library. The focus of this paper is however on academic law libraries. Academic law libraries are libraries established in faculties of law in institutions of higher learning such as the university and the Nigerian Law School (Anyaegbu, et al, 2013). According to them, the history of academic law libraries in Nigeria can be traced to the establishment of faculties of law in the university. In Nigeria, the training of lawyers starts properly at the university. They informed that legal education in Nigeria can be classified into two- academic and vocational. The academic stage which starts at the university, leads to the award of Bachelor of Laws (LL.B). The vocational stage is undertaken at the Nigerian Law School.Dada (2011) opined that the law library was designed to provide information for its teaming patrons in the legal profession. The legal profession which the law librarianship is designed to complement or service is dynamic. Law as a discipline is dynamic and keeps changing with changing times. Apart from the dynamic nature of law, the emergence of information and communication technology has revolutionarised both the way information resources are created, packaged and accessed. This has further complicated the role and services of the academic law library. The information needs of the legal profession are so demanding. It is upon this premise that Gilbert in Anaeme (2011) had opined that:there is no class of men, professional or otherwise so dependent upon books as the lawyers. There is no library of whatsoever kind or nature which so directly pertains to the interests which it’s designed to serve as the law library. I am speaking with authority when I say the lawyer’s books are his tools without which he would be unable to provide for himself and his family”Ekundayo (2000) reinforced the indispensability of the law library to both study the and practice when he said:what is anyone looking for in the legal profession anyway, if he does not intend keeping a good library. A lawyer is better off without a wig and gown, he may still make a living as a solicitor, legal executive or as an advocate appearing before those courts that carry on happily without robes. But with no library he would be sharing the fate of blind man holding a driver’s LicenseThe Role of Law Libraries in Dispensation of JusticeAnyaegbu& Dike (2016) stated that the law library is not only essential but crucial to the study and practice of the law. To meet the needs of its clientele effectively, the law library carries out the following functions:Collection DevelopmentCollection development is one of the fundamental functions every library performs. It is the aspect of the practice that is responsible for selecting, and acquiring information materials (Aina, 2004). Collection development management involves designing a collection development policy, selection, acquisition, conservation, preservation and weeding. It is the duty of the law librarian to select and acquire the necessary information resources in both print and non-print media pursuant to the needs of its users. This is achieved through various acquisition or collection development methods like purchase, gifts, bequeaths and exchange. Technological advancement of the 21st Century has enlarged the responsibility of the law library to include providing Internet access and web links to its user population.Organization of Resources An essential function of the law library is not only to acquire needed information resources but to also organize those resources for easy retrieval and use. It is in this regard, that every library provides tools to aid users to easily locate information resources in its collection. These tools include the various cataloguing and classification tools used in the production of the library catalogue and labelling of books on the shelf as well as shelf guides. The classification scheme in most academic law libraries in Nigeria is Moys Classification Scheme which is adapted to ease the use of legal literature in Nigeria. The catalogue entries are usually arranged by author, title and subject. The ICT option is also available to users via the Online Public Access Catalogue (OPAC).Circulation Services:Law Libraries provide circulation services such as lending, reservation and interlibrary loan services. The nature of law publication more especially law reports which comes in series does not allow them to be borrowed over a long period of time. Libraries usually give them out on short loan. Law libraries usually provide reprographic services to augment this handicap.Reference Services:According to Aina (2004), reference service is an important function of a library. Readers are provided this service on request. It is a person to person service because law library users’ reference queries differ. Sometimes the law librarian may have to interview the user to be able to define his need in order to ascertain the proper legal resources that will match his need. Reference sources abound in law. These include law dictionaries, encyclopaedia, citators, indexes to law reports, biographic sources, government publications and so on. In a computerized library setting, the law librarian has the option of manual or online searching.User Education : The role of law libraries in facilitating user education cannot be over emphasized. This is because user education is a key role of law libraries to enable access to library collection both in analog and or electronic library. This is done through the help of law librarians who are trained to render such services.Specialised Services:Law libraries market their services through specialized services such as Current Awareness Services (CAS) and Selective Dissemination of Information (SDI). Current Awareness service is a specialized service which a library renders to its patron to inform them about latest development in their subject area as soon as such materials arrive in the library. Such information can be conveyed to them through phone calls, e-mail messages, letters, preprints of papers, photocopy of table of contents, library bulletin, provision of list of recent acquisition, social media platforms and creating web links.Whereas Selective Dissemination of Information (SDI)is a customized service to law library user whose research profile is known to the law librarian. The whole essence is to promote the research effort of the user. It saves the user the time and problem of visiting the library and sieving through countless documents before getting relevant materials. Selective Dissemination of Information is better rendered via electronic media to reduce cost and delay in service delivery.Challenges Facing Faculty Law Libraries in NigeriaPaucity of Funds : Most public institutions in Nigeria face the problem of poor funding. Faculty of law libraries are no exception. Maintaining a virile law library is capital intensive because of the nature of legal materials which comes in volumes. Law is also dynamic. New laws emerge and old ones are either amended or repealed. Such changes should be reflected in the law library collection else the users may be misled.Shortage of Staff/Competency: Going by the requirement of Council of Legal Education in Nigeria, the law librarian in faculty of law should be law a lawyer and have professional qualification in librarianship. The inherent advantages in this dual qualification though commendable is hard to find in many academic law libraries in Nigeria. The lucrative legal practice often deters many lawyer librarians from choosing to serve in the library. Added to this is lack of continual training of law library staff in current library practice and Information and Communication Technology.Increase in ReadershipThe population of law library user continues to rise without a corresponding increase in the provision of law library facilities. This affects the reading spaces, ratio of reading materials per user as well as user satisfaction.Improper Collection BuildingCollection building in faculty of law is a joint responsibility of the library and the faculty. This is a requirement of Council of Legal Education. There is an existing standard for collection building in faculty of law libraries. The basic texts and facilities in the law library comes under scrutiny during the accreditation by both the Council of Legal Education and the National Universities Commission. In a study carried out by Onwudinjo (2015) in seven faculty libraries in South East Nigeria, he found that no law library in the Zone met the Council of Legal Education standards in both local and foreign law journals. Many faculty law libraries in Nigeria have either failed or denied accreditation in Nigeria.User Education Problem: Many law libraries in Nigeria have no formalized user education programmme for their users. Experience have shown that some databases prescribed by both the Council of Legal Education and the National Universities Commission when acquired are underutilized. In most cases they are acquired merely to scale through the accreditation exercise.Conclusion:An attempt has been made in this paper to highlight some of the basic role faculty of law libraries play in legal education in Nigeria. The paper also highlighted some of the challenges these libraries face while serving their users. Based on the issues raised recommendations were made on the way forward.RecommendationsIn the light of issues and challenges discussed, the following recommendations were made:Improved Funding. Paucity of fund in endemic in many libraries in Nigeria. Faculty of law libraries share the same budget with the main university library. This paper advocates a separate budget for the law library because of the serial nature of law reports and the rising cost of law publications. The budget should be jointly managed by the university librarian, the law librarian, and the Dean of Law for better accountability.Balanced Collection. Collection building in faculty of law library is built with the requirement of the Council of Legal Education and National Universities Commission in mind. Faculty of law libraries should adhere strictly to the requirements of these accrediting bodies one of which is to base the acquisition on the recommendation of the faculty members. This requires discipline discretion on the part of the library.User education. User education is sine quo non to effective utilisation of information resources in law. This is also embedded in one of the foundation courses (Legal Method) in law. The law librarian should ensure that law library users are exposed to the requisite media and information literacy skills. Practical sessions should also be organised in the library.Education and Training of Staff. The accrediting bodies require both professional qualification in law and librarianship for the law librarian. Acquisition of the two degrees takes several years, resources and effort. The authors recommend partial or full sponsorship for the law librarian to obtain these degrees. Similarly, every category of law library staff needs training and retraining on trending issues in law librarianship.Improved Facility. Facilities needed for modern practice of law librarianship in faculty of law libraries should be procured. Use of computers, Internet facilities and other ICT facilities in faculty of law libraries is imperative. ReferencesAina, L.O. (2004). Library and information science text in Africa. Ibadan: Third World Information Services Limited.Anyaegbu, M.I. (2013). Law libraries in information age: The role of academic law librarians. Information and Knowledge Management.3 (12)Anyaegbu, M.I. & Dike, V. (2016) Citation analysis of undergraduate in faculties of law libraries in Anambra and Enugu states of Nigeria. Education Research Journal.6 (7) p.85Dada, T.O. (2011). Law librarianship and legal research in the digital age. Lagos: Nigerian Institute of Advanced Legal Studies.Ekundayo, A. (2000) Legal hints 2nd ed. Lagos: Nigerian Institute of Advanced Legal Studies.Gilbert, F. B. (2011) In Anaeme, F.O. Law libraries, ICT resources for legal education and research. Current Issues in law library development. Abuja: Nigerian Association of Law Libraries.Onwudinjo, O.T. (2015) Law journal collections, accreditation issues and imperatives for lawLibraries. Library Philosophy and Practice (e. journal) Retrieved from:Onolaja, M.O. (nd). Problem of legal education in Nigeria. Retrieved from: www.alimiandco.com.Perruci, M. & Rothman, Y. (2010) image of librarianship in the 21th Century. Journal of Librarianship 3,2
Keywords: Law library; Legal Education; Legal Profession; Lawyers; Law Students